Education and fertility: Evidence from a policy change in Kenya - Luke E. Chicoine (Institute for the Study of Labor (IZA), 2012)
This paper investigates the relationship between women's education and fertility by exploiting a 1985 policy change in Kenya that lengthened primary school by one year. An instrumental variables approach measures the exogenous variation in treatment intensity across birth cohorts. The reform led to an increase in education, a delay in marriage, and reduced fertility beginning at the age of 20. The effect on fertility becomes increasingly negative through age 25. The findings suggest that postponement of marriage, reduction in the marital education gap, and increased early use of modern contraceptives contribute to reduced fertility. These results are consistent with women having greater control over their fertility decision.
Keywords: O15; J13; I25; 330; fertility; education; Kenya